PENGARUH HUBUNGAN POLITIK DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Pinandito, Dzulfikar Satria; Juliarto, Agung (Diponegoro Journal of Accounting, 2024)
This study aims to analyze the effect of political connection and corporate social responsibility on corporate tax aggressiveness. In this study, several control variables were used, namely firm size, leverage, and capital intensity.The population of this study is made up of manufacturing companies listed on the Indonesia Stock Exchange for the 2017–2019 period. The purposive sampling method was used to determine the sample in this study and obtained 79 companies, or 237 observations. This study uses the multiple regression analysis method to analyze the data.In this study, it was found that companies with board members, either commissioners or directors, having political connections tend to avoid tax aggressiveness and are more compliant with tax payments. The results of the study contradict the first hypothesis that was set. Meanwhile, the second hypothesis was accepted. Companies actively engaged in Corporate Social Responsibility activities tend to be more aggressive in terms of taxation.